Tendon transfers post wide resection of a left anterior calf malignant peripheral nerve sheath tumour in an 8-year-old girl with background of neurofibromatosis type-I and Li-fraumeni syndrome – A case report and surgical technique - Kenneth Pak Leung Wong; Mohammad Ashik bin Zainuddin; Arjandas Mahadev (Journal of Orthopaedic Reports)
Background: The advantages of an aggressive surgical approach outweigh its morbidity when managing malignant peripheral nerve sheath tumours (MPNST). The literature shows that adjuvant therapy has uncertain outcomes for disease survival and recurrence. We herein describe such a case affecting the left calf anterior compartment in an 8-year-old girl and its reconstruction. Case report: An 8-year-old girl with underlying neurofibromatosis type-I and Li-Fraumeni syndrome presents with a painful, rapidly growing left calf MPNST. She underwent wide resection and subsequent peroneus longus split transfer to reconstruct the anterior compartment and preserve ankle dorsiflexion. At 3 years post-operation, she is able to walk and run without complications. Conclusion: Peroneus longus split transfer is a viable option to maintain ankle dorsiflexion and allow normal gait following aggressive resection of the calf anterior compartment for MPNST in a child.